Beyond T2 and 3T: new MRI techniques for clinicians - Knowles, Benjamin R.; Friedrich, Florian; Fischer, Carola; Paech, Daniel; Ladd, Mark E. (Clinical and translational radiation oncology, 2019)
Technological advances in Magnetic Resonance Imaging (MRI) in terms of field strength and hybrid MR systems have led to improvements in tumor imaging in terms of anatomy and functionality. This review paper discusses the applications of such advances in the field of radiation oncology with regards to treatment planning, therapy guidance and monitoring tumor response and predicting outcome.
Gesehen am 26.08.2020